Heavy Metal Uptakes by Myriophyllum verticillatum from Two Environmental Matrices: The Water and the Sediment - Sapci, Zehra; Ustun, E. Beyza (TAYLOR & FRANCIS INC, 2015)
To determine the preferred elements of the benthic plant Myriophyllum verticillatum, changes in the element concentrations in the plant were investigated in laboratory condition. The reactor was fed with synthetically contaminated water consisting of 2 x 10(-6) M of the heavy metals Fe, Cr, Zn, Ni, and Cu for 1060 hours. The elements that were preferentially taken up by the tested plant body were evaluated with respect to translocation factor, bio-concentration factor, and the amounts of partial elements and relative uptakes. Both the changing physical properties of the aqueous solution in the reactor during the experiment and the growth of the plant were tested using a two-sample t-test. The Zn and Cu levels in the combination of the leaves and stems were found to be significantly higher than the levels in the roots at the end of the trial. Based on the partial amount of each element, the affinity of the plant for different elements was found to follow the order of Ca > Fe > Mn. Scanning electron microscope (SEM) analyses of the plant bodies indicated that these elements were located both inside the organs and on the surface of the tissues alone or with microorganisms such as diatoms.
Keywords: Myriophyllum verticillatum; elemental uptake; phytoremediation; CONTAMINATED SITES; SURFACE-WATER; ZN; CHROMIUM; CADMIUM; PB; CD; CU; LOCALIZATION; Environmental Sciences & Ecology